A cross sectional clinical study on correlation between myopia and intraocular pressure and ocular biometric values among adults in tertiary eye care in Palakkad, Kerala, India - A. M., Raja; A., Rajendraprasad; G., Seema (International Journal of Research in Medical Sciences, 2018)
Background: To find out whether there is a correlation between intra ocular pressure and ocular biometric values like corneal curvature, anterior chamber depth, lens thickness and vitreous chamber depth in myopic eyes. Methods: A cross sectional clinical study was conducted in karuna medical college hospital Palakkad Kerala, India from September 2015 to August 2017. 1000 eyes of 500 myopic patients attending the ophthalmology OPD were included in this study. Goldman applanation tonometry was used to measure intra ocular pressure. Bausch and Lomb keratometer was used to measure corneal curvature and Biometer A scan machine was used to measure anterior chamber depth, lens thickness, vitreous chamber depth and axial length. Results: In this study majority of the patients age group was 16-20 years. The overall mean intra ocular pressure was 15mmhg and mean radius of corneal curvature was 44.12D. In this study average anterior chamber depth was 3.55mm and mean lens thickness was 3.56mm.Mean vitreous chamber depth was 18.40. In this study mean axial length was 24.60mm. Conclusions: Amount of myopia and variation in corneal curvature was not statistically significant. There was no correlation between intra ocular pressure and degree of myopia. But anterior chamber depth, lens thickness, vitreous chamber depth and axial length were statistically very significant with amount of myopia.